Research on Religious Education in Nordic Countries : Introduction to Nordidactica 2015:2 - Bråten, Oddrun M.H. (Sør-Trøndelag University College, Trondheim, 2015)
This issue of the journal Nordidactica focuses on research in the field of religious education (RE). In Oddrun M. H. Bråten’s article, a methodology for comparative studies is presented and a comparative analysis conducted, centering on the use of the concepts of ‘learning about and from’ in Religious Education in England and Norway. In Jonathan Doney’s article we can read about the impact of the Ecumenical movement on the history of RE in England. Elisabet Haakedal discusses and compares two action research projects. Martin Ubani and a team of Finnish researchers present findings from research on RE teacher students. Gunnar J. Gunnarson and colleagues present findings from a study of Icelandic youths in a plural society, where they use theory of friendship and fear. Kathrine Kjærgaard provides us with insights into Greenlandic RE. In Mette Buchardt’s article, we can read about the role of Cultural Protestantism in developments in RE in Denmark, Sweden and Norway. Together these articles give a glimpse into the rich area of RE research today. In this introduction, I present the articles before offering some perspectives on the texts, promoting a more general discussion using my methodology as an analytical device.